Investigation Procedure for the Diagnosis of Historical Minarets: Inclined Minaret of Sivas Ulu Cami (Mosque) - İNCİ, PINAR; Halici, O.F.; Demir, C.; CÖMERT, MUSTAFA; Aldirmaz, B.; Coban, S.; Kiraz, F.; Kuran, F.; Berlucchi, N.; Iyisan, R.; Ilki, A. c (Springer Science and Business Media Deutschland GmbH, 2024)
The inclined minaret of Sivas Ulu Cami (Mosque) from the 13th century Danishmend Period is one of the most invaluable architectural heritages in Turkey. The extent of inclination of the minaret towards the North-West direction, the seismicity of the region, and structural damages that occurred in time have emphasized the need for comprehensive structural and geotechnical investigations. Accordingly, a rehabilitation project is currently going on under the coordination of the General Directorate of Foundations of Turkey. Within the scope of the project, first, a series of field surveys have been conducted to obtain the current features of the minaret including the characteristics of the structural system, damages, deviation from the vertical axis, ground conditions and foundation details. In addition to that, a monitoring system including inclinometers, linear potentiometers and accelerometers has been mounted for tracking the evolution of deformations and damages in time under environmental influences and extracting the dynamic properties of the minaret. Findings from the field survey and monitoring system were used for constructing an analytical model of the structural system of the minaret. Then nonlinear time history analyses were conducted under various strong ground motion records to estimate the seismic performance of the minaret when subjected to earthquakes of different characteristics. The results showed that the tensile stresses that occurred due to seismic actions exceeded the tensile strength of the brick masonry at the region of the transition segment and the cylindrical body (top level of the boot). © Tongji University Press 2024.
6th International Conference on Smart Monitoring, Assessment and Rehabilitation of Civil Structures, SMAR 2022
Keywords: Inclined; Masonry; Minaret; Rehabilitation; Seismic; SHM